Hubungan Hardiness dengan Locus of Control Eksternal pada Mahasiswa Perantauan dalam Menyelesaikan Skripsi - Marlinda, Iva Wuri; Supriono, Yoyon; Herani, Ika (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2015)
This study aimed to test the relationship between hardiness and external locus of control on the nomads student in completing the thesis. The population was undergraduate overseas student who is completing a thesis in the Faculty of Social and Political Sciences Brawijaya University. These samples included 135 nomads student. The sampling technique used purposive sampling technique. Hardiness and external locus of control was measured using a Likert scale, the scale of the two variables is made by the researcher. Data were analyzed with the Pearson's product moment correlation technique, with the result, there was significant a negative relationship between hardiness and external locus of control with the interpretation, the higher of hardiness, the lower level of external locus of control on the nomads student in completing the thesis and conversely. The correlation coefficient (r = 0.201) indicates that the relationship of hardiness with external locus of control, was a weak relationship.